Prevalensi Hipertensi pada Pasien Diabetes Melitus di Kelurahan Mojosongo Kota Surakarta - Ratna Herawati Prabowo (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Diabetes mellitus is a group of metabolic diseases with characteristic hyperglycemia. Diabetes Mellitus is a disease that cannot be cured but can be controlled. But if this disease is not treated properly, complications will arise; one of the complications of macroangiopathy in DM is hypertension, so the purpose of this study is to determine the prevalence of hypertension towards DM patients in the Mojosongo Surakarta area. The study was conducted at the Sibela Surakarta Health Center, with the subjects of DM patients being 50 people. The research design is a cross sectional approach with purposive sampling technique. The research instruments used were questionnaires and sphygmomanometer devices. To find out the prevalence a descriptive approach was used. The results showed that there were DM patients who were also diagnosed with hypertension. Hypertension prevalence in DM patients is 14 people (28%) from 50 samples, where the number of female patients is more than the male ones, which are 11 people (78.6%). While the prevalence based on age shows that most of the age is ≥ 61 years, which are as many as 8 people (57.2%). For the prevalence based on the duration of the disease, it was found that as many as 9 people (64.3%) had suffered DM more than 10 years. The presence of DM patients accompanied by hypertension, with a prevalence of 14 people (28%).